PENDIDIKAN BERBASIS BIMBINGAN DAN KONSELING ISLAM DALAM PSIKOLOGI KONSELING - Trinurmi, Hj. Sitti (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
Humans are the perfect creation of Allah compared to other creatures. It was marked by the completeness of reason and passion possessed by humans. Intellect is the potential possessed by humans to distinguish what is good and what is bad, while lust is a tendency or human desire to have everything in human life, including a tendency to do things that deviate. Intellect and lust are what in human life always experience upheaval between the whisper of reason and the whisper of lust. The struggle of struggle between the whisper of reason and the whisper of lust is a problem in human life which is faced from time to time. The complexity of the problematic has brought and directed some people to experience conflicts and obstacles in fulfilling their worldly desires, and can even cause mental stress that can disrupt life’s stability. Islamic guidance is one of the efforts and strategies in order to help individuals overcome conflicts in human life, as well as efforts to improve the spiritual quality of human beings. In the world of education, students are a group that is very vulnerable and difficult to avoid the very complex life problems. That is caused by the potential of the intellect possessed by students still in the developmental stages so that the curiosity tends to be greater. This is what makes most of the students who fall into deviant behavior. From the reality of the problems that occur above gives a general picture that with the increase in science and technology it is not enough to realize eternal happiness. Therefore, to form an Islamic young generation, the implementation of Islamic guidance and counseling for students is seen as very strategic in order to reduce the deviant behavior of students at school. The application of the Islamic guidance and counseling system to schools is a manifestation of the concern of the school to reduce deviant behavior among its students. In its application, Islamic guidance and counseling carried out in schools must be guided by the Koran and Hadith.